Room-temperature photoluminescence in structurally disordered SrWO4 - Anicete-Santos, M.; Picon, F. C.; Escote, M. T.; Leite, E. R.; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2006)
Intense and broad visible photoluminescent (PL) band in structurally disordered SrWO4 compounds was observed at room temperature. The polycrystalline scheelite strontium tungstate (SrWO4) samples prepared by the polymeric precursor method at different temperatures of annealing were structurally characterized by x-ray diffraction and Fourier transform Raman spectroscopy measurements. Quantum-mechanical calculations showed that the local disorder in the cluster of the network modifiers Sr has a very important role in the charge transfer. The experimental and theoretical results are in good agreement, indicating that the generation of the intense visible PL band can be related to short-range order-disorder degree in the scheelite structure. (c) 2006 American Institute of Physics.